A Case Report: Effect of Robotic Exoskeleton Based Therapy on Neurological and Functional Recovery of a Patient With Chronic Stroke - Singh, Neha; Saini, Megha; Kumar, Nand; Srivastava, M. V. Padma; Kumaran, S. Senthil; Mehndiratta, Amit (Frontiers in Neurology, 2021)
BACKGROUND: A novel electromechanical robotic-exoskeleton was developed in-house for distal-joints for post stroke rehabilitation. The objective was to explore the functional MRI and the neurophysiological changes in cortical excitability in response to exoskeleton training for 9 year chronic-stroke. CASE-REPORT: The study involved a 52-year old female patient with a 9-year chronic-stroke of the right-hemisphere, who underwent 20 therapy-sessions of 45 minutes each. Cortical- excitability and clinical-scales: Fugl-Mayer (FM), Modified Ashworth Scale (MAS), Brunnstrom-Stage (BS), Barthel-Index (BI), Range of Motion (ROM), were assessed pre-and post-therapy to quantitatively assess the motor recovery. CLINICAL OUTCOMES: Increase in FM wrist/hand by 6, BI by 0 and decrease in MAS by were reported. Ipsilesion Motor Evoked Potential (MEP) (obtained using Transcranial Magnetic Stimulation) was increased by 98μV with a decrease in RMT by 6% and contralesional MEP was increased by 43μV with a decrease in RMT by 4%. Laterality Index of Sensorimotor Cortex (SMC) reduced in precentral- gyrus (from 0.152 to -0.707) and in postcentral-gyrus (from 0.203 to -0.632) with an overall change of ~0.85 in SMC demonstrating substantial shift in activation towards ipsilesional-hemisphere. Exoskeleton- based training might push the limits of recovery in chronic stroke.